Analisis Kesalahan pada Siswa dalam Memodelkan Soal Cerita Materi Sistem Persamaan Linear Tiga Variabel - Hana, Sesi; Putra, Muhammad Satria Eko; Indriani, Vina; Sari, Vera Yolanda; Aisyah, Hafsah Ainun; Rahmawati, Melly; Nurhasanah, Nurhasanah (Innovative: Journal Of Social Science Research, 2025)
This study aims to identify students' errors in modeling story problems on SPLTV material using the Newman analysis approach. This study was conducted at SMAN 6 Bengkulu City involving 36 students of class X F as subjects. Data were collected through a written test with two HOTS-based questions. Error analysis was carried out using Newman indicators, including reading, understanding, transformation, process skills, and writing/encoding errors. The results showed that students faced various obstacles, especially in understanding questions and converting information into mathematical models. The main factors causing errors were a lack of understanding of basic algebraic concepts, being less careful in reading questions, and minimal practice of story-based questions on SPLTV material. These findings provide recommendations for teachers in developing more effective learning strategies to overcome student obstacles.